Middle Eastern Consumers’ Perceptions Towards Medical Tourism In Thailand. - Landreville, Pamela (The Bangkok Medical Journal, 2016)
OBJECTIVE: This research study aimed to explore Middle Eastern consumers’ perceptions toward medical tourism in Thailand. Middle Eastern citizens represent major clients for Thai private hospitals and a better understanding of their perception is valuable to stakeholders to improve services to ensure patients’ satisfaction and sustainability. MATERIALS AND METHODS: The sample consisted of respondents from the Middle East region obtained by convenience sampling in Bangkok, Thailand, Delhi, India, and Dubai, U.A.E. The employed research instruments comprised structured survey questionnaires and in-depth interviews. The quantitative data collected were analyzed through the use of SPSS. RESULTS: Findings from this research study first demonstrated that Middle Eastern consumers (96%) have a positive perception towards the quality of health care in Thailand. They (81%) also perceive that Thai hospitals offer a wide range of medical procedures, which positively influence their perception of the health care system’s efficiency. Only 43.3% of consumers surveyed agreed that health care in Thailand is well promoted and marketed abroad. CONCLUSION: Findings from this research study include increased competition from emerging medical tourism destinations and the current economic situation in the Middle East. The recommendation is to review marketing and services (including prices) displayed and offered to the Middle Eastern clientele.